DSM-5 Attenuated Psychosis Syndrome in Adolescents Hospitalized With Non-psychotic Psychiatric Disorders - Salazar de Pablo, Gonzalo; Guinart, Daniel; Cornblatt, Barbara A.; Auther, Andrea M.; Carrión, Ricardo E.; Carbon, Maren; Jiménez-Fernández, Sara; Vernal, Ditte L.; Walitza, Susanne; Gerstenberg, Miriam; Saba, Riccardo; Lo Cascio, Nella; et al. (Frontiers in Psychiatry, 2020)
Introduction: Attenuated psychotic symptoms form the criteria to identify individuals at increased clinical risk of developing psychosis. The study of individuals with these symptoms has led to the release of the DSM-5 diagnosis of Attenuated Psychosis Syndrome (APS) as a condition for further research. Although attenuated psychotic symptoms often occur for the first time during adolescence, studies focusing on adolescents are scarce. We aimed to characterize and compare hospitalized adolescents with DSM-5-APS diagnosis versus hospitalized adolescents without a DSM-5-APS diagnosis. Methods: Interviewing help-seeking, hospitalized adolescents (aged 12-18 years) and their caregivers independently with established research instruments, we (1) evaluated the presence of APS among non-psychotic adolescents, (2) characterized and compared APS and non-APS individuals regarding sociodemographic, illness and intervention characteristics, (3) correlated psychopathology with levels of functioning and severity of illness and (4) investigated the influence of individual clinical, functional and comorbidity variables on the likelihood of participants to be diagnosed with APS. Results: Among 248 consecutively recruited adolescents (age=15.4±1.5 years, females=69.6%) with non-psychotic psychiatric disorders, 65 (26.2%) fulfilled APS criteria and 183 (73.8%) did not fulfil them. Adolescents with APS had higher number of psychiatric disorders than non-APS adolescents (3.5 versus 2.4, p<0.001; Cohen’s d=0.77), particularly, disruptive behavior disorders (Cramer’s V=0.16), personality disorder traits (Cramer’s V=0.26), anxiety disorders (Cramer’s V=0.15), and eating disorders (Cramer’s V=0.16). Adolescents with APS scored higher on positive (Cohen’s d=1.5), negative (Cohen’s d=0.55), disorganized (Cohen’s d=0.51), and general symptoms (Cohen’s d=0.84), and were more severely ill (Cohen’s d=1.0) and functionally impaired (Cohen’s d=0.31). Negative symptoms were associated with lower functional levels (Pearson ρ=−0.17 to −0.20; p=0.014 to 0.031). Global illness severity was associated with higher positive, negative, and general symptoms (Pearson ρ=0.22 to 0.46; p=0.04 to p<0.001). APS status was independently associated with perceptual abnormalities (OR=2.0; 95%CI=1.6-2.5, p<0.001), number of psychiatric diagnoses (OR=1.5; 95%CI=1.2-2.0, p=0.002), and impaired stress tolerance (OR=1.4; 95%CI=1.1-1.7, p=0.002) (r2=0.315, p<0.001). Conclusions: A considerable number of adolescents hospitalized with non-psychotic psychiatric disorders meet DSM-5-APS criteria. These help-seeking adolescents have more comorbid disorders and more severe symptoms, functional impairment, and severity of illness than non-APS adolescents. Thus, they warrant high intensity clinical care.